Analysis of additive manufacturing (AM) multi material behaviour using numerical simulation with experimental verification - Abd Rahman, Azri Rahimi (2025)
The field of Metal Additive Manufacturing (MAM) has made significant strides, especially in creating components with diverse material properties. Wire Arc Additive Manufacturing (WAAM) offer numerous advantageous over the conventional manufacturing process suchas producing AM's components with distinctly localized mechanical and metallurgical properties commonly known as functional grading. Previous studies have shown that the hardness of WAAM structures varies along the building direction, primarily due to effect of process parameters and the thermal gradient between the deposited layers. This can be attributes to the formation on non-equilibrium phase transformation. A precise hardness prediction considering the phase fraction with the Finite Element Method (FEM) requires optimal material data which can be measured from Time Temperature Transformation (TTT) and Continuous Cooling Transformation (CCT) diagrams.